Hydroxyapatite Coating on Alloys CoCrMo-TiN with Sol-Gel Method - Charlena Charlena; Sulistioso Giat Sukaryo; Moch. Irgham Zuhfria (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
ABSTRACTHydroxyapatite is synthesized by precipitation-sonification using calcium from field snail shell and powder phosphorus from (NH4)2HPO4. The calcium value was measured by atomic absorption spectrophotometer was 82.82%.The temperatures were varied on 600, 800, and 1000 oC to determine the best temperature of the coating. The best temperature was used to superimpose the HAp on the CoCrMo-TiN metal alloy using the modified sol-gel method. The layer on the metal alloy was identified with x-ray diffraction (XRD) and corrosion test. The XRD result showed that most of the CoCrMo-TiN metal alloy surface was coated by HAp. Beside HAp, there were several other phases such as calcium phosphate, carbonate apatite type A and type B. The best result of the corrosion test was showed in CoCrMo-TiN metal alloy coated with HAp with the smallest corrosion rate 0.0082 mpy.Keywords: hydroxyapatite, CoCrMo-TiN, precipitation-sonification, sol-gel modified